(untitled) (Estudos em Design, 2019)
Quadro Editorial Editores Cristina Portugal Rita Maria de Souza Couto Avaliadores desta edição v. 27, n. 3 (2019) Alexandre Santos de Oliveira Alexandre Farbiarz Álvaro José Barbosa Sousa Ana Veronica Pazmino Andréa Almeida Andrea Sousa Antonio Ferreira Colchete Filho Bárbara Necyk Beany Monteiro Cássia Letícia Carrara Cristina Portugal Daniel Portugal Daniel Raposo Daniel Wyllie Rodrigues Gisela de Campos Edson Rufino de Souza Eloiza Andrade Corrêa Fernanda Abreu Frederico Braida Helena Barbosa Haroldo Gallo Ione Bentz Jackeline Farbiarz Juliana Bueno Luiz Agner Luiza Novaes Marcos Braga Maria José Jorente Mariana Padua Mariano Lopes de Andrade Neto Maristela Mitsuko Ono Paula Landim Raimundo Diniz Ranielder de Freitas Rogério José Câmara Sandra Regina Rech Sandra Souza Sydney Freitas Tomás Barata Virginia Borges Kistmann